2020
DOI: 10.1371/journal.pone.0227470
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ proteomics reveals the regulatory response to Magnaporthe oryzae in durable resistant vs. susceptible rice genotypes

Abstract: Rice blast disease caused by Magnaporthe oryzae (M. oryzae) is one of the most serious diseases. Although previous research using two-dimensional gel-based proteomics to assess the proteins related to the rice blast resistance had been done, few proteins were identified. Here, we used the iTRAQ method to detect the differentially expressed proteins (DEPs) in the durable resistant rice variety Gangyuan8 (GY8) and the susceptible rice variety Lijiangxintuanheigu (LTH) in response to M. oryzae invasion, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The quantitative protein ratios, which require that a protein contains at least one unique peptide, were weighted and normalized by the median ratio in Mascot (Ma et al . 2020). When the difference was >1.2‐fold, it was regarded as a significantly different protein ( P ≤ 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative protein ratios, which require that a protein contains at least one unique peptide, were weighted and normalized by the median ratio in Mascot (Ma et al . 2020). When the difference was >1.2‐fold, it was regarded as a significantly different protein ( P ≤ 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, proteomics studies have revealed the roles of DUF26, nucleotide binding-leucine rich repeat, PRs, ROS productionscavenging enzymes, heat shock proteins (HSPs), nuclear reorganization-related proteins, TFs, and phytohormone signaling in rice resistance, whereby proteins related to pathogen perception and signal transduction are important during the early stage of infection (for review, see Meng et al 2019). A recent study using iTRAQ found that probenazole-inducible protein 1 (PBZ1) and phenylpropanoid accumulated in both resistant and susceptible cultivars, which was in contrast to reports from previous studies utilizing the 2DE approach (Ma et al 2020b). Interestingly, a metabolomic assay using HPLC identified a rice saponin, Bayogenin 3-O-cellobioside, which is the first saponin found in rice (Norvienyeku et al 2020).…”
Section: Response Of Rice To Fungimentioning
confidence: 97%
“…Moreover, ABA signaling influences the calcium (Ca 2+ ) signaling that is considered as a front line of signaling events and is involved in resistance response of rice against M. oryzae (Wang et al 2019). In a proteomics study of resistant Gangyuan8 (GY8) and susceptible Lijiangxintuanheigu (LTH) cultivars infected by M. oryzae, Ca 2+ − dependent protein kinase, Ca 2+ sensor calmodulin, and calmodulin-like protein were particularly found upregulated in LTH but remained the same in GY8, suggesting that the proteins possibly regulate blast resistance negatively in those cultivars (Ma et al 2020b). Another proteomics study found several Ca 2+ -binding proteins in saliva of phloem-feeding insects and honeydews of BPH and green rice leafhopper, supporting the function of Ca 2+ -binding proteins in counteracting the sieve-tube occlusion defenses in host plants (Will et al 2013;Zhu et al 2020).…”
Section: Common Metabolites and Specific Metabolites Upon Each Bioticmentioning
confidence: 99%
“…The implementation of the model makes it possible to identify time intervals that contribute to plant infection and the development of a pathogen, as well as to evaluate the intensity of the pathogen exposure during this time period, expressed as a percentage of probability (%). Such time periods are called excess, and the number of excesses during the study period describes the intensity of the manifestations of rice blast [14]. Estimating the number of excesses during the pre-growing and growing periods will help to identify the intensity of the influence of the environment and agroclimatic conditions on the dynamics of the pathogen Pyricularia oryzae Cav.…”
Section: Methods Of Researchmentioning
confidence: 99%